THE EFFECT OF EDUCATIONAL VIDEOS ON ADOLESCENTS’ KNOWLEDGE AND ATTITUDES TOWARD THE RISKS OF EARLY MARRIAGE AT MAN 2 PADANG CITY - Lifaniura, Lushiana; Aprianti, Ety; Muthia, Gina (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Early marriage remains a serious problem in Indonesia, impacting reproductive health, education, and the future of adolescents. One preventative measure is providing education about the risks of early marriage through engaging learning media, such as educational videos. This study aims to determine the effect of educational videos on adolescents' knowledge and attitudes about the risks of early marriage at MAN 2 Padang City. This study used a pre-experimental, one-group pre-post test design. The population was 555 grade X students, with a sample size of 78. The sampling technique used systematic random sampling at MAN 2 Padang City was conducted from February to August 2025. Univariate and bivariate analyses used the Wilcoxon test. The results showed that the mean knowledge score before the program was 10.44. The mean knowledge score after the program was 13.47. The mean attitude score before the program was 31.23. The mean attitude score after the program was 34.15. There is an effect of educational video on knowledge (p=0.000). and attitudes in adolescents (p=0.000). Conclusion There is an effect of educational video on knowledge and attitudes in adolescents at MAN 2 Padang City. It is recommended that adolescents actively seek out and watch educational videos and that institutions implement BRUS programs in schools.